Production and chemical composition of hydrophytes cultivated in aquaponics - Martínez-Yáñez, Alicia del Rosario; Albertos-Alpuche, Pedro J.; Guzman-Mendoza, Rafael; Robaina-Robaina, Lidia E.; Alvarez-Gonzalez, Alfonso; Diaz-Plascencia, Daniel (Ecosistemas y Recursos Agropecuarios, 2018)
Aquaponics can be defined as the integration of hydroponic plant production in a recirculating aquaculture system and has been proposed as a sustainable method to control the accumulation of waste produced by fish farming. The objective of the present study was to determine the biomass production and its feed potential of Myriophyllum aquaticum, Limnobium laevigatum, Lemna minor and Salvinia molesta grown in aquaponics. To evaluate the chemical compositions of these species, dry matter, organic matter, crude protein, neutral detergent ber, acid detergent ber, lignin, ash, ether extract, gross energy, calcium, and phosphorus of the aquatic plants were determined. Based on the results of this study, aquatic plants are considered to fulfll most of the nutritional requirements of productive animal species. Therefore, it is feasible to use them as the main ingredient in whole animal rations, with an emphasis on Myriophyllum aquaticum and Lemna minor as alternative food sources for di erent animal species, opening the way to aquaponic fodder production. Aquatic plants are interesting alternative, unconventional feed sources, especially because their high growth rates and nutritional qualities make it feasible to use them for animal consumption. However, Salvinia molesta has no value as fodder, especially because of its lignin concentration, which could affect the fodder digestibility.